Prevalence of epidermal growth factor receptor (EGFR) mutations and correlation with histological patterns in lung adenocarcinoma in patients from Bosnia and Herzegovina - Dalma Udovičić-Gagula; Nejra Džananović; Mirsad Dorić (Medicinski glasnik, 2023)
Aim: Lung adenocarcinoma (ADC) is a leading subtype of lung cancer, histologically defined with five different architectural growth patterns: lepidic, acinar, papillary, solid and micropapillary. The aim of this study was to explore the prevalence of epidermal growth factor receptor (EGFR) mutation and a relationship between the specific histological patterns of lung ADC in the population of Bosnia and Herzegovina. Methods: The study included tumour tissue from 102 patients with completely resected lung ADC from 2015 to 2020. Molecular testing for the presence of EGFR mutations was performed by real-time PCR method. The relationship between EGFR mutation status and clinicopathological parameters was analysed. Results: The EGFR mutation was detected in 12 (11.8%) cases of ADC, more often in non-smokers (p=0.007). A higher percentage of solid growth pattern presented in ADC may be an indicator of EGFR negativity (p=0.039), while a higher percentage of micropapillary growth pattern more common in the presence of EGFR mutation (p=0.047). Conclusion: The prevalence of EGFR mutation is in accordance with the expected prevalence considering our studied population, Caucasians from South Europe. Better understanding of the relationship between histological patterns and molecular characteristics of lung ADC will enable earlier diagnosis and optimal treatment for patients.
Keywords: architectural growth pattern; oncogenic mutation; lung cancer